Juxta-adrenal schwannoma presenting as a giant adrenal tumor: A case report and a literature review. (2018) - Abdessater, Maher; El Mokdad, Mohammad; Gas, Jerome; Sleiman, Walid; Coloby, Patrick; Bart, Stephane
Highlights: Retroperitoneal schwannomas (RS) are rare, benign tumors that originate in the neural sheath. RS can be misdiagnosed preoperatively, especially when they stick to other structures (the adrenal in our case). Complete surgical resection is the treatment of choice and open surgery is the safest option when we have big tumors. Histology and Immunohistochemistry confirm the diagnosis. Abstract: Introduction: Retroperitoneal schwannomas (RS) are rare, benign tumors that originate in the neural sheath. Juxta-adrenal schwannomas may be misdiagnosed with giant adrenal tumors. This article reports the case of a RS that presented as an asymptomatic adrenal mass in a 50 Y.O female. Presentation of case: An abdominal ultrasound of our asymptomatic patient showed right adrenal lesion of 9 cm of diameter. Endocrinological evaluation was negative. The patient was considered to have a non-secreting right adrenal mass confirmed by adrenal scan. We began a right laparoscopic trans peritoneal adrenalectomy, but when we discovered intra operatively that the wall of the IVC and the renal vein were very adherent to the mass which had a lot of small vessels that were bleeding, we converted to open surgery that allowed us to remove the mass safely. The operative time was 200 min, the blood loss was 850 cc and the patient was discharged uneventfully on the sixth day after surgery. Discussion: Although we thought that we removed a huge adrenal tumor from the retroperitoneum of our patient, the pathological exam revealed a RS that comprises the adrenal gland which was normal. Preoperative establishment of diagnosis is difficult in case of RS that can be misdiagnosed, especially when they stick to other structures (the adrenal in our case). Conclusion: Complete surgical resection is the treatment of choice for RS and open surgery is the safest option when we have big tumors. Histology and Immunohistochemistry confirms the diagnosis that can be easily missed preoperatively.